2003
DOI: 10.1128/iai.71.9.5097-5103.2003
|View full text |Cite
|
Sign up to set email alerts
|

Serum Opacity Factor (SOF) ofStreptococcus pyogenesEvokes Antibodies That Opsonize Homologous and Heterologous SOF-Positive Serotypes of Group A Streptococci

Abstract: Serum opacity factor (SOF) is a protein expressed by Streptococcus pyogenes that opacifies mammalian serum. SOF is also a virulence factor of S. pyogenes, but it has not been previously shown to elicit a protective immune response. Herein, we report that SOF evokes bactericidal antibodies against S. pyogenes in humans, rabbits, and mice. Rabbit antiserum against purified recombinant SOF2 opsonized SOF-positive M type 2, 4, and 28 S. pyogenes in human blood but had no effect on SOF-negative M type 5 S. pyogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…Sof is regarded as a major virulence factor that is known to contribute to pathogenesis of streptococcal infection in animal models (Courtney & Pownall, 2010). The sof gene was first sequenced over 15 years ago (Rakonjac et al, 1995) and its product was found to be a surface bound protein of over 100 kDa, with a C-terminal domain comprised of numerous repeating peptides that bound to both fibronectin and fibrinogen (Courtney et al, 2003;Courtney & Pownall, 2010). End point RT-PCR found that the genes encoding both of these proteins were differentially expressed in response to treatment with a sublethal dose of manuka honey.…”
Section: Discussionmentioning
confidence: 99%
“…Sof is regarded as a major virulence factor that is known to contribute to pathogenesis of streptococcal infection in animal models (Courtney & Pownall, 2010). The sof gene was first sequenced over 15 years ago (Rakonjac et al, 1995) and its product was found to be a surface bound protein of over 100 kDa, with a C-terminal domain comprised of numerous repeating peptides that bound to both fibronectin and fibrinogen (Courtney et al, 2003;Courtney & Pownall, 2010). End point RT-PCR found that the genes encoding both of these proteins were differentially expressed in response to treatment with a sublethal dose of manuka honey.…”
Section: Discussionmentioning
confidence: 99%
“…However, conclusions were drawn without knowledge of the sfbX gene located downstream of sof, which was most likely also affected by the mutation strategy. An additional matrix-binding activity of fibrinogen was found to map to the repetitive domain at the C terminus of the SOF molecule (6), and SOF was shown to elicit antibodies with opsonizing activity toward heterologous SOF types (9). SOF and SfbX are both involved in adherence of GAS to immobilized fibronectin (20).…”
mentioning
confidence: 99%
“…That bacterial reduction was due to antibody-mediated opsonizing killing and not to bacterial aggregation by specific antibodies was demonstrated by performing a previously described assay [19]. Briefly, 5 10 3 CFU of GAS strain A20 was added to serum isolated from either GAS-vaccinated BALB/c or C3H/HeN mice or non-immune control mice and rotated for 3 h at 37°C.…”
Section: Humoral Immune Responses Elicited In Genetically Susceptiblementioning
confidence: 99%